Cathelicidin-WA Facilitated Intestinal Fatty Acid Absorption Through Enhancing PPAR-γ Dependent Barrier Function - Zong, Xin; Cao, Xiaoxuan; Wang, Hong; Xiao, Xiao; Wang, Yizhen; Lu, Zeqing (Frontiers in Immunology, 2019)
The molecular mechanisms underlying the cellular uptake of long-chain fatty acids and the regulation of this process have been debated in recent decades. Here, we established an intestinal barrier dysfunction model in mice and Caco2 cell line by Lipopolysaccharide (LPS), and evaluated the fatty acid uptake capacity of the intestine. We found that LPS stimulation restricted the absorption of long chain fatty acid (LCFA), while Cathelicidin-WA (CWA) pretreatment facilitated this physiological process. At the molecular level, our results demonstrated that the stimulatory effects of CWA on intestinal lipid absorption were dependent on cluster determinant 36 and fatty acid transport protein 4, but not fatty acid–binding protein. Further, an enhanced intestinal barrier was observed in vivo and in vitro when CWA alleviated the fatty acid absorption disorder induced by LPS stimulation. Mechanistically, peroxisome proliferator-activated receptor (PPAR-γ) signaling was considered as a key pathway for CWA to enhance LCFA absorption and barrier function. Treatment with a PPAR-γ inhibitor led to impaired intestinal barrier function and suppressed LCFA uptake. Moreover, once PPAR-γ signaling was blocked, CWA pretreatment could not maintain the stability of the intestinal epithelial cell barrier or LCFA uptake after LPS stimulation. Collectively, these findings suggested that PPAR-γ may serve as a target for specific therapies aimed at alleviating fatty acid uptake disorder, and CWA showed considerable potential as a new PPAR-γ agonist to strengthen intestinal barrier function against fatty acid malabsorption.